PREDICTING FINANCIAL STATEMENTS CORPORATE FRAUD: BENEISH M-SCORE MODEL - Hariri Hariri; Ayub Wijayati Sapta Pradana; Sri Luki Widjajanti (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2017)
This research aims to detect fraudulent financial statements the financial statements of XYZ, PT in the period 2010-2013. This research is a qualitative descriptive research. Data collection techniques used are observation and documentation. Data analysis techniques used are data reduction, data presentation and conclusion with Beniesh M-Score Model. The results showed that the financial statements in the period 2010-2013 as a whole that Beniesh M-Score XYZ, PT reached -3.94 in 2010, 0.70 in 2011, -3.32 in 2012 and -2.38 in 2013, the overall Beniesh M-Score reached above -2.22 except in 2011. Beniesh M-Score Model indicates that the management has performed the practice of manipulating numbers on the financial statements conducted continuously in the period of 2010, 2012 and 2013. The authors suggest the regulation (tax office) and public accounting firms, namely that the regulators do a review/inspection directly on the company's assets that has been recorded in the financial statements and the external auditor who has been appointed to conduct an examination of the financial statements to be more independent and do detection of financial statements using ratio analysis.Keywords: Detection, Fraudulent Financial Statements, Beneish M-Score Model, Practice of Manipulation Number